2011
DOI: 10.1017/s0022112011000127
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian mixing in straight compound channels

Abstract: Recently Stocchino & Brocchini (J. Fluid Mech., vol. 643, 2010, p. 425 have studied the dynamics of two-dimensional (2D) large-scale vortices with vertical axis evolving in a straight compound channel under quasi-uniform flow conditions. The mixing processes associated with such vortical structures are here analysed through the results of a dedicated experimental campaign. Time-resolved Eulerian surface velocity fields, measured using a 2D particle-image velocimetry system, form the basis for a Lagrangian anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 31 publications
6
51
0
Order By: Relevance
“…As suggested by Nezu et al [1999] and verified by Stocchino and Brocchini [2010], the dynamics of the flow field and, hence, of the vorticity, strongly depends on the flow characteristics in terms of the flow‐depth ratio r h , between the depth in the main channel ( hmc* ) and the depth in the floodplains ( hfp* ) as first introduced by Shiono and Knight [1991] and later modified by Nezu et al [1999]. In a more recent contribution, Stocchino et al [2011] investigated the different dispersion regimes occurring in compound channel flows and highlighting the dependence of mixing both on the depth ratio r h and on the subcritical/supercritical character of the flow, i.e., on the Froude number ( Fr ).…”
Section: Introductionmentioning
confidence: 91%
“…As suggested by Nezu et al [1999] and verified by Stocchino and Brocchini [2010], the dynamics of the flow field and, hence, of the vorticity, strongly depends on the flow characteristics in terms of the flow‐depth ratio r h , between the depth in the main channel ( hmc* ) and the depth in the floodplains ( hfp* ) as first introduced by Shiono and Knight [1991] and later modified by Nezu et al [1999]. In a more recent contribution, Stocchino et al [2011] investigated the different dispersion regimes occurring in compound channel flows and highlighting the dependence of mixing both on the depth ratio r h and on the subcritical/supercritical character of the flow, i.e., on the Froude number ( Fr ).…”
Section: Introductionmentioning
confidence: 91%
“…Spanwise and vertical velocities at interface show the maximum in magnitude at the junction of the main channel and the floodplain in both the channels. However, in symmetric channel, the spanwise interface velocity at the junction is of opposite direction indicating the presence of two horizontal vortices of equal strength but opposite in nature (Stocchino et al 2011). Similarly, a horizontal vortex is seen to be formed near the junction in asymmetric channel also.…”
Section: Spanwise and Vertical Flow Velocity At Interface (V 0 W 0 )mentioning
confidence: 89%
“…2.4, which shows macrovortices in the transition regions and a mean flow velocity distribution along the transversal direction (see Stocchino et al 2011). Recent experimental investigations (Stocchino and Brocchini 2010), which were based on use of the PIV technique, revealed that the population and properties of macrovortices largely depend on the typical depth gradients, i.e., on the ratio r h between the largest and smallest flow depths.…”
Section: Turbulence Evolving On the Horizontal Planementioning
confidence: 95%
“…The mixing induced by these dynamical domains can be described in terms of both absolute (single-particle) and relative (e.g., particle pairs) statistics (e.g., Provenzale 1999;LaCasce 2008;Stocchino et al 2011). Typically, under shallow flow conditions, macrovortices strongly influence the growth in time of the total absolute dispersion after an initial ballistic regime after their formation, leading to a (a) (b) Fig.…”
Section: Turbulence Evolving On the Horizontal Planementioning
confidence: 99%
See 1 more Smart Citation